ANALYSIS OF RAW MATERIAL INVENTORY CONTROL BASED ON ECONOMIC ORDER QUANTITY METHOD AT PT. SAWITINDO MAS TANJUNG RAJA SAKTI, LAMPUNG - Henokh Xaverius Winata; Iskandar Ali Alam (ZILLZELL MEDIA PRIMA, 2024)
This research aims to determine the price difference used with the EOQ method, save production costs, and produce maximum results. The research uses random sampling techniques, the method in this research uses qualitative methods and secondary data sources, data collection methods namely observation and interviews. Population In this research, there were all 40 employees of PT Sawitindo, the sample used was 3 employees who were directly interviewed. The data analysis technique used in this research was using the EOQ and total cost methods. The contribution of research using the EOQ method is that it can save production costs at PT and produce optimal quantities. The results obtained by calculating the EOQ method are in September IDR 2,935,749 in October IDR 3,501,849, in November IDR 3,945,896. After using the EOQ method there is a large price difference, namely in September IDR 814,251, in October IDR 1,748,151, and in November IDR 804,104, In general, research using the EOQ method can produce maximum results with more cost effective.